Outcomes of Endovascular Therapy for Upper Extremity Peripheral Artery Disease With Critical Hand Ischemia. (October 2016) - Tomoi, Yusuke; Soga, Yoshimitsu; Fujihara, Masahiko; Iida, Osamu; Shintani, Yoshiaki; Zen, Kan; Ando, Kenji
Purpose: To investigate the clinical outcomes of endovascular therapy (EVT) for upper extremity peripheral artery disease (PAD) with critical hand ischemia (CHI).Methods: A subanalysis was performed of multicenter registry data on 36 consecutive patients (mean age 65.7±10.3 years; 19 men) who underwent EVT from January 2003 to December 2013 for angiographically diagnosed de novo upper limb PAD with CHI in 40 limbs. Fifty percent of patients had diabetes, and two-thirds were on hemodialysis. Technical success of EVT was straight-line flow to the hand and final residual diameter stenosis ≤50% for balloon angioplasty alone and ≤30% without flow-limiting dissection for subclavian artery stenting. The primary outcome was 12-month amputation-free survival [AFS; freedom from a composite of major (above-the-wrist) amputation and death]. The 12-month secondary outcomes were overall survival, limb salvage, freedom from major adverse limb events (MALE; major amputation or any repeat revascularization of the limb), and wound healing (complete epithelialization without death or major amputation).Results: Initial success was achieved in 87% (35 of 40 limbs); 1 patient experienced puncture site problems, and 3 (8%) of 36 patients (4 treated limbs) died within 30 days. Hand symptoms were alleviated in 37 (92%) limbs. The mean follow-up was 26.8±27.8 months. Seven fingers (5 limbs) underwent phalanx amputations and 2 limbs had an amputation above the wrist. Complete wound healing was achieved in only 5 (19%) of 26 surviving patients at 12 months. At 1 year, the Kaplan-Meier estimates for AFS, overall survival, limb salvage, and freedom from MALE were 56.4%, 59.4%, 93.1%, and 78.5%, respectively. Univariate analysis revealed that the predictors of AFS at 1 year were diabetes (p=0.03), hemodialysis (p<0.001), PAD (p=0.003), and the presence of a wound (p<0.001). During follow-up, 20 (56%) patients died; a cardiovascular cause accounted for 40% of deaths.Conclusion: Endovascular therapy for upper limb PAD with CHI was technically successful and alleviated symptoms in the majority of cases, but the prognosis of patients with CHI was extremely poor in real-world clinical practice.